Feeding and Management of Horses with and without Free Faecal Liquid: A Case–Control Study - Katrin M. Lindroth; Jan-Erik Lindberg; Astrid Johansen; Cecilia E. Müller (Animals, 2021)
Free faecal liquid (FFL) in horses is characterised by the excretion of faeces in two phases (one solid and one liquid), which may cause dermatitis on the hindlegs. The causes of FFL are not known. Results from previous studies have indicated that feed ration composition and management factors may play important roles in the occurrence of FFL. A case–control study was therefore performed in which data on feed rations, feeding practices and management factors were compared between horses with (case) and without (control) FFL on 50 private farms in Sweden and Norway. The comparisons show that case and control horses were reported to be fed similar average amounts of wrapped forage (p = 0.97) and to be subject to similar management practices, but case horses were fed higher proportions of concentrates in their diet (p < 0.001) and lower average amounts of straw and lucerne (p < 0.05) compared to control horses. Case horses were reported to be fed twice as much concentrate per 100 kg BW and day as control horses and a higher daily intake of starch and water-soluble carbohydrates (p < 0.05). Case horses also had a lower daily intake of digestible crude protein and neutral detergent fibre compared to control horses (p < 0.05). These differences were small but are of interest for further studies of factors causing FFL.